Conversion of the Ms70 alpha-brass torsion-test data into hot-forming processing maps - Kubina, Tomáš (Materiali in tehnologije, 2013)
The present paper gives a summary of the plastic behaviour of the Ms70 deep-drawing cartridge brass under the hot-forming conditions explored by using a SETARAM-Vítkovice torsion plastometer. The specimens were cut from the hot-extruded and, subsequently, cold-drawn brass bars. Formability tests were performed on the diameter 6 mm specimens at (650, 700, 750, 800 and 850) °C and at the speeds of (16, 80, 400 and 800) r/min. These testing conditions are equivalent to the conditions of the ordinary industrial hot extrusion of brass: the single most problematic operation in the manufacturing process in terms of an occurrence of serious defects. The results of the torsion tests were converted into the conventional format: the maximum flow-stress levels vs. the peak-strain intensity. The points thus obtained can be used for finding the activation energy for forming Q, which is useful for determining the thermally compensated strain rate with the aid of the Zener-Hollomon Z parameter. The power-dissipation maps with the axes showing the deformation temperature and logarithmic strain rate were computed using a dynamic material model. The calculation of the dissipation efficiency was verified by comparing it with the known data on the 30 % zinc brass. The maps constructed in this manner allow the data from the torsion and compression plastometers tobe compared. The paper also includes a discussion of the changes in the processing maps at higher strains showing the optimum regions for the hot extrusion of brass.
Keywords: flow stress; vroče preoblikovanje kovin; medi; brass; tečenje; hot formability; strain rate; torsion test; power-dissipation maps